Strengthen the peasant collectives in the Ecuadorian Andes. Analysis from the provinces of Chimborazo and Cotopaxi - RebaÏ, Nasser (2018)
For thirty years, the rural territories of the Ecuadorian Andes have been affected by a process of agricultural “modernization”. While the productive specializations and the massive use of chemical pesticides had disastrous effects on the environment, the decline of collective practices and the disorganization of peasant groups reinforced the social and economic vulnerability of family farming. This article aims to illustrate this critical situation by basing on the results of fieldworks carried out in the provinces of Chimborazo and Cotopaxi. A specific analysis will show to what extent the generalization of the use of pesticides is a key factor of the vulnerability of the rural territories in the Ecuadorian highlands. Then, a discussion will be opened about the need to promote or strengthen the peasant collectives in order to bring out projects of sustainable territories